Parameter-dependent robust stability for nonlinear distributed delay stochastic systems with polytopic-type uncertainties - Wen-Hua Gao; Fei-Qi Deng (2009 International Conference on Machine Learning and Cybernetics, 2009)
The robust stability problem for nonlinear distributed delay stochastic systems with polytopic-type uncertainties is discussed. Based on parameter-dependent Lyapunov-krasovs-kii functional and free-weighting matrix method, a delay-dependent and parameter-dependent stability condition is presented in terms of linear matrix inequalities. The result in this paper improves the existing stability criteria and has less conservativeness. The simulation example shows that the result is effective.